Cover Image, Volume 79, Issue 3. Issue 3 (May 2018) - Puglisi, Melany P.; Bradaric, Michael J.; Pontikis, John; Cabai, Jonathan; Weyna, Theodore; Tednes, Patrick; Schretzman, Robert; Rickert, Karl; Cao, Zhao; Andrei, Daniela
Abstract : The cover image, by Melany Puglisi et al., is based on the Research Article Novel primary amine diazeniumdiolates: chemical and biological characterization, DOI:10.1002/ddr.21428 .